Solving the Issue of Ionizing Radiation Induced Neurotoxicity by Using Novel Cell Models and State of the Art Accelerator Facilities - Schielke, Celine; Hartel, Carola; Durante, Marco; Ritter, Sylvia; Schroeder, Insa S. (Frontiers in Physics, 2020)
Cognitive dysfunction induced by ionizing radiation remains a major concern in radiation therapy as well as in space mission projects. Both fields require sophisticated approaches to improve protection of the brain and its neuronal circuits. Radiation therapy related research focusses on advanced techniques imposing maximal effect on the tumor while minimizing toxicity to the surrounding tissue. Research for example has led to the revival of spatially fractionated radiation therapy (SFRT) and the advent of FLASH radiotherapy. To investigate the influence of the space radiation environment on brain cells, low dose, high LET radiation in addition to simulated microgravity have to be studied. Both research areas, however, call for cutting-edge cellular systems that faithfully resemble the architecture of the human brain, its development and its regeneration to understand the mechanisms of radiation-induced neurotoxicity and their prevention. In this review, we discuss the proposed mechanisms of neurotoxicity such as the loss of complexity within the neuronal networks, vascular changes, or neuroinflammation. We compare the current in vivo and in vitro studies of neurotoxicity including animal models, animal and human neural stem cells, and neurosphere models. Particularly, we will address the new and promising technique of generating human brain organoids and their potential use in radiation biology.